Obstructing Justice: The Association Between Prosecutorial Misconduct and the Identification of True Perpetrators - Weintraub, Jennifer N. (Crime & delinquency, 2020)
Prosecutorial misconduct is a potential barrier to identifying true perpetrators of crimes in wrongful conviction cases. Previous theories posit that pressures on prosecutors to carry out their role as ministers of justice in an adversarial system can incentivize misconduct and disincentivize postconviction cooperation, especially regarding alleged misconduct at trial. This study empirically tests how prosecutorial misconduct at trial can affect postconviction proceedings by analyzing the relation between prosecutorial misconduct alleged at trial and the identification of a true perpetrator postconviction in DNA exoneration cases. Results demonstrate that, as predicted, prosecutorial misconduct is associated with a decrease in the odds of true perpetrator identification. This work further underscores the need for the implementation of functional policy to deter prosecutorial misconduct.